If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -4) + (2x + 1) = 0 Reorder the terms: (-4 + 3x) + (2x + 1) = 0 Remove parenthesis around (-4 + 3x) -4 + 3x + (2x + 1) = 0 Reorder the terms: -4 + 3x + (1 + 2x) = 0 Remove parenthesis around (1 + 2x) -4 + 3x + 1 + 2x = 0 Reorder the terms: -4 + 1 + 3x + 2x = 0 Combine like terms: -4 + 1 = -3 -3 + 3x + 2x = 0 Combine like terms: 3x + 2x = 5x -3 + 5x = 0 Solving -3 + 5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 5x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 5x = 0 + 3 5x = 0 + 3 Combine like terms: 0 + 3 = 3 5x = 3 Divide each side by '5'. x = 0.6 Simplifying x = 0.6
| 8(x+2)=7x-7 | | 1.35p=40.5 | | -4+x=6+x | | 3n=14-4 | | 27=x+1+(2x+1)+5x | | 14-(5m+8)=2+3m-12 | | 9x+7y=-9 | | 9x+(-2x)= | | 3n+6=3 | | y=2x^2+9x+7 | | r(x)=10x-.002x^2 | | 27=x+1+2x+1+5x | | 57+x+x+132=165 | | 4x+12(7+x)= | | 6(y+3)+5=47 | | 54n-8=3 | | 3x+20=2x-15 | | 6x+5-2x=2(2x+3) | | 2x^2=x-8 | | f(x)=2x^3-7x^2+13x+40 | | 5(2-5x)-2(3-7x)=10-x+6 | | 5(y+2)+2=32 | | 63=7M+13 | | 3x-15+3x=5+6x-20 | | 2x-7-3x=-5 | | 7+25x=20x+8 | | 2x^2=-8+10x | | 9x+40=-15x-8 | | 8p-27=-7+3 | | 5sinx-1=-2 | | 5k+4.9-1.2K-1.5K+2= | | 2x+76+x+112=36 |